An online Arabic vocabulary learning games prototype in IIUM - Sahrir, Muhammad Sabri; Alias, Nor Aziah (2010)
This is an online Arabic vocabulary learning games prototype which is specifically designed for elementary learners at pre-university level at Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). The design and development of games prototype are based on the methods and approaches of design and development research (Richey & Klein, 2007), which was formerly known as developmental research (Richey, Klein & Nelson, 2004). This method is also known as designed case (Reigeluth & Frick, 1999), designbased research (Reeves, 2006 & Herrington, et. al, 2007), formative research (Nieveen, 2007), design research (Bannan- Ritland, 2003; Van der Akker, 2007). It begun with the analysis of 3 theories from literature based on the work of Nation (2003), Prensky (2001) and Mayer (2001). This game-based learning prototype allows the lecturers and students to use it as an additional learning aid to learn Arabic language in a gaming application, in addition to traditional learning methods.